2011
DOI: 10.1128/jvi.02143-10
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of a Novel Motif Conserved across Geminivirus Rep Proteins

Abstract: Members of the Geminiviridae have single-stranded DNA genomes that replicate in nuclei of infected plant cells. All geminiviruses encode a conserved protein (Rep) that catalyzes initiation of rolling-circle replication. Earlier studies showed that three conserved motifs-motifs I, II, and III-in the N termini of geminivirus Rep proteins are essential for function. In this study, we identified a fourth sequence, designated GRS (geminivirus Rep sequence), in the Rep N terminus that displays high amino acid sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 75 publications
2
101
0
1
Order By: Relevance
“…Within the MSRV Rep we identified various amino acid motifs previously identified in other mastreviruses including (1) a likely rolling-circle replication (RCR) motif I sequence (FLTYP [11]), (2) a possible metal ion coordination domain (HLHVLLQ, corresponding to RCR motif II [11]), (3) a possible GRS motif (YHPNIQASR [14]), (4) a possible RCR motif III sequence (YILKSP [11]), (5) a probable dNTP-binding domain sequence (VGX 4 GKTTW 30 DD [8]), (6) a retinoblastoma-related protein binding motif (LHCYE [27]), and (7) a potential oligomerisation domain (SAERLFPTLPSPFV [10]; Supplementary Fig. 2).…”
Section: Monocot Infecting Mastrevirusesmentioning
confidence: 99%
“…Within the MSRV Rep we identified various amino acid motifs previously identified in other mastreviruses including (1) a likely rolling-circle replication (RCR) motif I sequence (FLTYP [11]), (2) a possible metal ion coordination domain (HLHVLLQ, corresponding to RCR motif II [11]), (3) a possible GRS motif (YHPNIQASR [14]), (4) a possible RCR motif III sequence (YILKSP [11]), (5) a probable dNTP-binding domain sequence (VGX 4 GKTTW 30 DD [8]), (6) a retinoblastoma-related protein binding motif (LHCYE [27]), and (7) a potential oligomerisation domain (SAERLFPTLPSPFV [10]; Supplementary Fig. 2).…”
Section: Monocot Infecting Mastrevirusesmentioning
confidence: 99%
“…3). In addition, the GRS motif, composed of 12 consensus amino acids and possibly involved in rolling circle initiation in several geminiviruses (Nash et al, 2011), was found between aa 77 and 99 of this AGV protein ( Fig. 3), thus indicating that the latter had the typical features of a geminivirus Rep. With regard to the other AGVencoded proteins, Pfam (Finn et al, 2014) search detected conserved domains expected for geminiviral proteins, with the exception of AGV V2 (Table S4).…”
Section: Genome Organization Of Agv and Phylogenetic Analysesmentioning
confidence: 99%
“…BLASTP analysis of the Rep protein (352 aa, encoded by C1 ORF) showed 74% amino acid sequence identity with Rep of East African cassava mosaic virus-Kenya (EACMV-KE, a begomovirus). The motifs FLTYP (motif I), HLH (motif II) and YIEKG (motif III), reported in other geminivirus Rep proteins and required for dsRNA binding, protein conformational changes and viral DNA cleavage (Nash et al, 2011), were identified at aa 18, 60 and 106 of AGV Rep, respectively (Fig. 3).…”
Section: Genome Organization Of Agv and Phylogenetic Analysesmentioning
confidence: 99%
“…A more detailed analysis showed that Rep proteins encoded by MMDaV contain the motifs reported in other geminivirus Reps (Fig. S3), which include: (i) the rolling-cycle replication (RCR) motif I (FLTFP), required for specific dsDNA binding; (ii) the RCR motif II (HFH), a metal-binding site that may be involved in protein conformation and DNA cleavage; (iii) the RCR motif III (YIQKE), a catalytic site for DNA cleavage (Nash et al, 2011); (iv) the Walker A (GPT-RSGKT) and the Walker B (LYNVIDDI) domains that are crucial components of the nucleotide-binding site (Walker et al, 1982) (Fig. S3).…”
Section: Y Ma and Others 2426mentioning
confidence: 99%